(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted in the peri urban areas of Surat city of Gujarat. Total fifty buffalo farm owners were randomly selected and interviewed for the questionnaire prepared about improved buffalo husbandry practices adopted by them. The findings indicated that majority of buffalo farm owners had medium adoption level on different component of improved buffalo husbandry practices viz. 72% for housing, 74% for feeding, 64% for breeding, 68% for healthcare, 74% for milking management and 74% for calf rearing. The overall adoption levels of the respondents in improved buffalo husbandry practices fall under low, medium and high categories are 18%, 66% and 16%, respectively. The adoption index of different aspect of improved buffalo husbandry practices of housing, feeding, breeding, health care, milking and calf rearing were 49.4, 34.3, 67, 52.5, 55.9 and 63.7%, respectively and overall adoption index of improved buffalo husbandry practices was 53.8% which indicated moderate adoption level of buffalo farm owners in the study area.